2016
DOI: 10.1007/s10858-016-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid addition of unlabeled silent solubility tags to proteins using a new substrate-fused sortase reagent

Abstract: Many proteins can’t be studied using solution NMR methods because they have limited solubility. To overcome this problem, recalcitrant proteins can be fused to a more soluble protein that functions as a solubility tag. However, signals arising from the solubility tag hinder data analysis because they increase spectral complexity. We report a new method to rapidly and efficiently add a non-isotopically labeled Small Ubiquitin-like Modifier protein (SUMO) solubility tag to an isotopically labeled protein. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Moreover, the activity of SaSrtA has been improved using directed evolution approaches, resulting in tetramutant enzyme that is ~140-fold more active than the native SaSrtA (Chen et al, 2011). Additional rate enhancements have been achieved by altering the reaction conditions and by fusing the nucleophile substrate to SaSrtA (Amer, Macdonald, Jacobitz, Liauw, & Clubb, 2016). The reader is referred to a number of excellent reviews describing the use of sortase as a bioconjugation reagent (Proft, 2010; Tsukiji & Nagamune, 2009; Wu & Guo, 2012).…”
Section: In Vitro Transpeptidation Activitymentioning
confidence: 99%
“…Moreover, the activity of SaSrtA has been improved using directed evolution approaches, resulting in tetramutant enzyme that is ~140-fold more active than the native SaSrtA (Chen et al, 2011). Additional rate enhancements have been achieved by altering the reaction conditions and by fusing the nucleophile substrate to SaSrtA (Amer, Macdonald, Jacobitz, Liauw, & Clubb, 2016). The reader is referred to a number of excellent reviews describing the use of sortase as a bioconjugation reagent (Proft, 2010; Tsukiji & Nagamune, 2009; Wu & Guo, 2012).…”
Section: In Vitro Transpeptidation Activitymentioning
confidence: 99%
“…Both N- and C-terminal fusions have been described, typically in the context of new approaches for recombinant protein expression and purification [3, 2430]. Of these, fusions at the N-terminus are particularly intriguing as it has been suggested that the N-termini of these constructs can access the enzyme active site in an intramolecular fashion, thereby driving transpeptidation due to the increase in local reactant concentration [3, 27, 30]. As an example, Amer et al demonstrated an increase in ligation rates when a construct consisting of wild-type SrtA staph fused at its N-terminus to an aminoglycine-containing SUMO module was reacted with a separate LPXTG substrate [3].…”
Section: Optimizing Srtastaph Performancementioning
confidence: 99%
“…Of these, fusions at the N-terminus are particularly intriguing as it has been suggested that the N-termini of these constructs can access the enzyme active site in an intramolecular fashion, thereby driving transpeptidation due to the increase in local reactant concentration [3, 27, 30]. As an example, Amer et al demonstrated an increase in ligation rates when a construct consisting of wild-type SrtA staph fused at its N-terminus to an aminoglycine-containing SUMO module was reacted with a separate LPXTG substrate [3]. In this case, reaction rates involving the SUMO-SrtA staph fusion were significantly enhanced relative to a control reaction involving separate SrtA staph , aminoglycine SUMO, and LPXTG substrate.…”
Section: Optimizing Srtastaph Performancementioning
confidence: 99%
See 2 more Smart Citations